PENGARUH BOND RATING TERHADAP RETURN SAHAM PERUSAHAAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) - DARMESTI, ARI (Jurnal Akuntansi AKUNESA, 2014)
This study investigate the impact of bond rating on stock return. This study uses the sample of listed companies in Indonesia Sharia Stock Index (ISSI) and rated by PT Pefindo during 2011-2013. Sample of this study covers 20 samples stable/downgrade and 4 samples upgrade. The analysis of this research were performed using Spearman’s rho (rs) and two independent samples tests using Mann Whitney Test. The result showed that partially only the stable/downgrade bond rating that have impact on stock return. However, simultaneously showed that no significant difference on average abnormal stock return between stable/downgrade bond rating and upgrade bond rating.Keyword: bond rating, stock return, even study, upgrade, downgrade